The evaluation of optimal product positions - Klaus Brockhoff (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1982)
Marketing managers who are confronted with solutions from optimal product positioning models may well doubt whether it is possible to transfer results as given into the market place. Some reasons for that are shortly presented. It is then suggested to calculate the deviations from the optimal Solution by one-dimensional, two-dimensional or multi-dimensional analyses. These can be used to evaluate the stability of product positions, especially the stability of optimal product positions. A simple measure of Solution stability is introduced along with suggestions for its use in decision making.
Keywords: 650